(3GdQMdI GdMLGRjIs - (3YHO Gddg Hf eMeO Hf CHj HcQ GdYjGTj, CHh SGde,J (B1090 (3g` s
(3ChdgG (B:s
(3GdQH QH hGdYHO YHO jGdjJ TYQi ef Gdecda Ef bdJ YHO aPGc ejJ ChbdJ QH Cfnj jcda s
(3BNQgG (B:s
(3hhUdfG HdOfG Cefg Gddg jhe GdCQHYGAXgQkG , SGHY YTQ ThGd SfI CQHY hSHYjf hCda hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B479s
(3HgG JeRjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B129 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B112s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B464 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B711 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B191 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs